The effectiveness of parental assistance-based online learning model on self-efficacy - Andy Sapta; Muhammad Aizuddin Ab Alim; Ami Hibatul Jameel; Abd Gafur (International Journal of Evaluation and Research in Education (IJERE), 2024)
The obstacles experienced during online learning are inevitable circumstances. Hence, students need to have motivational beliefs that they have the ability to thrive in online learning despite its difficulties. Applying parental-based online learning is expected to help students increase their self-efficacy. This study examines the effect of using an online learning model based on parental assistance on students’ self-efficacy with a quantitative approach. This type of research is quasi-experimental, with a pre and post-test control group design by studying seventh-grade students in several public junior high schools in Kisaran. The study found that applying an online learning model based on parental assistance improved students’ self-efficacy more than a conventional online learning model. Consequently, parental assistance will make a practical contribution to the implementation of learning, especially in the implementation of online learning in the era of the pandemic and after the COVID-19 pandemic.